2017
DOI: 10.1071/an15006
|View full text |Cite
|
Sign up to set email alerts
|

An integrated sensory, consumer and olfactometry study evaluating the effects of rearing system and diet on flavour characteristics of Australian lamb

Abstract: Producing lamb with good eating quality – flavour, tenderness and juiciness – is essential for consumer satisfaction. Forages such as lucerne and plantain can play an important role in sustainable lamb production; however, it is important to ensure that these feeds do not introduce undesirable flavours. We evaluated the potential for backgrounding (post-weaning) and finishing diets (11 weeks pre-slaughter) to affect lamb eating quality. Lambs were backgrounded on either (1) a combination of three cultivars of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 66 publications
4
42
0
Order By: Relevance
“…Pyrazines are nitrogen-containing heterocyclic compounds that are formed through the Maillard reaction (Mottram, 1998). They have a "grilled meat" or "roasted" odor note, low vapor pressure and low odor threshold (Table 1) and have been previously reported, following GC-olfactometry, (GC-O) as important odor-impact volatiles in cooked lamb muscle (Frank et al, 2017;Resconi et al, 2010;Watkins, Frank, Singh, Young, & Warner, 2013). In agreement with the data relating to pyrazines, the sensory study (Gkarane et al, 2017) using the same animals as those used in this study showed that lamb from castrates had higher (P < 0.05) Intensity of Roast Meat Aroma and Intensity of Roast Meat Flavor than lamb from rams.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrazines are nitrogen-containing heterocyclic compounds that are formed through the Maillard reaction (Mottram, 1998). They have a "grilled meat" or "roasted" odor note, low vapor pressure and low odor threshold (Table 1) and have been previously reported, following GC-olfactometry, (GC-O) as important odor-impact volatiles in cooked lamb muscle (Frank et al, 2017;Resconi et al, 2010;Watkins, Frank, Singh, Young, & Warner, 2013). In agreement with the data relating to pyrazines, the sensory study (Gkarane et al, 2017) using the same animals as those used in this study showed that lamb from castrates had higher (P < 0.05) Intensity of Roast Meat Aroma and Intensity of Roast Meat Flavor than lamb from rams.…”
Section: Resultsmentioning
confidence: 99%
“…(); (17) Frank et al. (); (18) Frank et al. (); (19) Giri, Osako, Okamoto, and Ohshima (); (20) Göğüş, Özel, and Lewis (); (21) Kochhar (); (22) Kondjoyan and Berdagué (); (23) Madruga et al.…”
Section: Methodsmentioning
confidence: 99%
“…Other minority VOC were also found in suckling light lambs such as 1-pentanol (Vieira et al 2012). Ethyl acetate has a positive relationship with barnyard odour (Frank et al 2017). Alkyl pyrazines such as 2,5 dimethyl pyrazine have a very low odour threshold (Fors and Olofsson 1985).…”
Section: Volatile Compoundsmentioning
confidence: 97%
“…2-pentyl furan was also found in suckling lambs fed MR (Mor an et al 2014). This VOC is associated with beany, grassy (Drumm and Spanier 1991) and liver (Frank et al 2017) flavour.…”
Section: Volatile Compoundsmentioning
confidence: 97%
See 1 more Smart Citation